Improving Parent's Knowledge on Toddler Teeth Development and Risk Faktor of Caries using KAGISAKU Card - Rr. Pipiet Okti Kusumastiwi; Wustha Farani (Jurnal Kesehatan Gigi, 2026)
Early childhood caries (ECC) remains a prevalent public health issue in Indonesia. One of the key determinants in its prevention is parental knowledge of toddler tooth development and associated risk factors. This study aimed to evaluate the effectiveness of the “Kartu Gigi SehatKu” (KAGISAKU) card in improving parents’ knowledge. This quasi-experimental study employed a pretest–posttest design with a non-equivalent control group. A total of 84 parents of toddlers were divided into intervention (received training and KAGISAKU card) and control (received standard posyandu education) groups. Knowledge was measured using a standardized questionnaire before and six weeks after the intervention. Data were analyzed using paired t-test, independent t-test, and ANCOVA. A significant increase in knowledge scores was observed in the intervention group (Δ = 38.5 ± 8.1; p < 0.001) compared to the control group (Δ = 5.4 ± 4.5). The effectiveness of the intervention was consistent across gender, education level, and socioeconomic status. In summary, the KAGISAKU card effectively improved parental knowledge of toddler tooth development and caries risk factors across diverse educational and socioeconomic backgrounds, highlighting its potential as an accessible and scalable preventive oral health education strategy in community health settings such as posyandu